The ameliorative effect of Apium graveolens & curcumin against Non-alcoholic fatty liver disease induced by high fructose-high fat diet in rats - Areeg M. Abd‐Elrazek; Shaimaa R. Ibrahim; Heba A. El‐dash (SpringerOpen, 2022)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is a condition resulting from fat aggregates in liver cells and is associated with metabolic syndrome, obesity, and oxidative stress. The present work was designed to investigate the role of celery and curcumin against high-fructose-high-fat (HFHF) diet-induced NAFLD in rats. Thirty male rats were classified into five groups: GP1: control group (rats were fed a normal control diet), GP2: HFHF group as a positive control (rats were fed a HFHF diet) for 20 weeks, GP3: HFHF + sily group, GP4: HFHF + celery group, and GP5: HFHF + cur group (rats in 3, 4, and 5 were treated as in the HFHF group for 16 weeks, then combined treatment daily by gavage for 4 weeks with either silymarin (as a reference drug, 50 mg/kg bw) or celery (300 mg/kg bw) or curcumin (200 mg/kg bw), respectively. The progression of NAFLD was evaluated by estimating tissue serum liver enzymes, glycemic profile, lipid profile, oxidative stress markers in liver tissue, and histopathological examination. Moreover, DNA fragmentation and the released lysosomal enzymes (acid phosphatase, β-galactosidase, and N-acetyl-B-glucosaminidase) were estimated. Results Our results showed that HFHF administration for 16 weeks caused liver enzymes elevation, hyperglycemia, and hyperlipidemia. Furthermore, increased hepatic MDA levels along with a decline in GSH levels were observed in the HFHF group as compared to the control group. The results were confirmed by a histopathological study, which showed pathological changes in the HFHF group. DNA fragmentation was also observed, and the lysosomal enzyme activities were increased. On the other hand, oral supplementation of celery and cur improved all these changes compared with positive control groups and HFHF + sily (as a reference drug). Moreover, celery, as well as curcumin co-treatment, reduced HFHF-enhanced DNA fragmentation and inhibited elevated lysosomal enzymes. The celery combined treatment showed the most pronounced ameliorative impact, even more than silymarin did. Conclusion Our findings suggest that celery and curcumin consumption may exhibit ameliorative impacts against NALFD progression, while celery showed more ameliorative effect in all parameters.